First xenacanthid shark from the Pennsylvanian (Moscovian) of the Northern Caucasus (Russia) - O. Hampe; A. Ivanov (Fossil Record, 2007)
The occurrence of Triodus teberdaensis n. sp. teeth from the Pennsylvanian Tolstiy Bugor Formation (Moscovian) of Karachay-Cherkess Republic is the first evidence of xenacanthid remains from the Caucasus. The new species was found in carbonate sediments interpreted as resulting from short-term transgressions during the Pennsylvanian regressive phase – further evidence that xenacanthids, predominantly adapted to freshwater, have also lived in marine environments.Das Auftreten von Zähnen des Triodus teberdaensis n. sp. in der oberkarbonischen Tolstiy Bugor Formation (Moscovium) von Karatschai-Tscherkessien ist der erste Nachweis xenacanthider Überreste aus dem Kaukasus. Die neue Art wurde in karbonatischen Sedimenten, die als Transgressions-Intervalle innerhalb der globalen Oberkarbon-Regression interpretiert werden, abgelagert – ein Beleg dafür, dass die überwiegend aus Süßwasserablagerungen bekannten Xenacanthiden auch im marinen Milieu lebten.doi:10.1002/mmng.200700004